CN69 Reducing fear and stress through educational interventions during therapeutic procedures in children and adolescents with cancer: A systematic review - Michail, Koralia; Tistsi, Theologia; De Munter, J.; Charalambous, Andreas (My University, 2022)
Therapeutic procedures in hospitalized children and adolescents with cancer comprise a source of stress and anxiety. Educational interventions have demonstrated favorable results in children undergoing these procedures although solid guidance for children and adolescents with cancer remains scarce. We aimed to explore the effectiveness of educational interventions in children and adolescents undergoing cancer therapy.